ANALISIS MINAT SISWA TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA - Piska Ayu Andira; Andriani Utami; Mirli Astriana; Ahmad Walid (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
This study aims to determine the Student Interest Analysis of Student Learning Outcomes In Learning of Natural Sciences. The things that want to be discussed in this study are: How student interest in learning affects student learning outcomes in science subjects at SD Muhammadiyah Durian Sebatang, Kedurang District. So this study uses a quantitative approach with a survey method. Sampling research amounted to 27 respondents. The results of this study are student interest in learning has a positive effect on student learning outcomes and causes good learning outcomes, interest in learning in terms of all indicators that influence, student interest in learning is included in one of the internal factors also has a close relationship to student learning outcomes. With the percentage of students who are very interested there are 4 (14.81%) with high learning outcomes, 12 students (44.4%) with moderate learning outcomes, 8 students who are quite interested (29 ,63%) with moderate learning outcomes, 3 students who are less interested (11.11%) with low learning outcomes. High learning interest in students will lead to good learning outcomes, and good learning outcomes are caused by high student interest in learning.